Contrasting abundance and contribution of clonal proliferation to the population structure of the corkscrew sea anemone Bartholomea annulata in the tropical Western Atlantic. Issue 1 (March 2017) - Titus, Benjamin M.; Daly, Marymegan; Macrander, Jason; Del Rio, Annelise; Santos, Scott R.; Chadwick, Nanette E.
Abstract: Clonal propagation is an important life history trait for many sessile organisms, and often leads to the formation of monoclonal aggregations. In the marine environment, sea anemones have been model species for testing theory regarding the evolution of sex and understanding the contribution of sexual versus asexual reproduction to the population structure in facultatively clonal animals. However, little attention has been paid to tropical actiniarians. The corkscrew anemone Bartholomea annulata is common in tropical marine habitats in the western Atlantic and Caribbean; it forms small aggregations (2–4 anemones) on coral reefs and larger aggregations (>10 anemones) in mangrove habitats. We used field surveys and molecular analyses to investigate patterns of distribution, abundance, and genetic structure of aggregations formed by B. annulata on a reef in the US Virgin Islands and in a unique mangrove habitat in the Florida Keys. Abundance was greatest at the abandoned rock quarry mangrove habitat in the Florida Keys, where anemones formed continuously distributed aggregations carpeting the exposed limestone walls. Genetic diversity assessed via intersimple sequence repeats (ISSRs) and six microsatellite loci revealed that asexual reproduction plays only a minor role in the formation of both small and large anemone aggregations. Specifically, ISSR analyses showed that only ~10% of anemone aggregations were clonal in the US Virgin Islands, while microsatellite genotyping identified clonality in only 1 of 35 aggregations. In the Florida Keys, only four clonal genotypes were recovered within aggregations, but eight clones, representing 33% of the total surveyed population, had individuals in multiple aggregations. Thus, population structure of B. annulata appears to rely primarily on sexual reproduction, although asexual reproduction may play a nontrivial role in some environments. Mechanisms that drive the formation of genotypically diverse aggregations remain unknown, but may include attraction toward conspecifics, shared use of preferred habitats, or the local retention of larvae in partially enclosed habitats.